Manajemen Strategi Kepala Sekolah dalam Pengembangan Lembaga Pendidikan Islam di SMA Darul Ulum Unggulan Badan Pengkajian Penerapan Teknologi (BPPT) Jombang - Abd. Haris; Nazilatul Masruroh (Jurnal Kependidikan Islam, 2011)
The strategy management of headmaster has important role to increase education quality to manage human resource education (external and internal). More over, the headmaster role has responsible to increase the existence of institute that he leads. The headmaster must gives response to develop his institute. The previous reasons is a basic reason why the researcher do the research The result of this research shows the development of islamic institute consists of increasing educative officer, increasing facilities, supervising student, and creating religious atmosphere. However, the development includes making decision through discuss together, and inserting responsibility value to all staffs. The factors that support the development of the institution are . professional educative administrator, religious atmosphere, complete facilities, antuism andKigKest trust of society. From the explanation above the researcher summarize the professioruil and democratic headmaster needed to develop the qualified institution because it can move all of the school substancesand components maximally. Beside the development of scKool, it is needed working together all of the school components because a school is a collective system which can not work alone witlwut participationall of aspects. The increasing of education quality is a demand that mitst be realized. The headmaster has to increase concrete steps to increase the education quality continuously because if the institution is notqualified, the society will leave it. It will be dangerous and all people don't want it is happened.